2010
DOI: 10.1371/journal.pone.0012610
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Relationship between VEGF and BMI Independent of Insulin Sensitivity by Glucose Clamp Procedure in a Homogenous Group Healthy Young Men

Abstract: BackgroundThis is the first study to experimentally explore the direct relationship between circulating VEGF levels and body mass index (BMI) as well as to unravel the role of insulin sensitivity in this context under standardized glucose clamp conditions as the methodical gold-standard. In order to control for known influencing factors such as gender, medication, and arterial hypertension, we examined a highly homogeneous group of young male subjects. Moreover, to encompass also subjects beyond the normal BMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
55
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 33 publications
9
55
0
7
Order By: Relevance
“…Adipose tissue is considered to be an endocrine organ and releases hormones, enzymes and cytokines, including VEGF and IL-6 [14,15]. In 2010, Loebig et al observed a positive correlation between BMI and serum VEGF level [15]. A similar result was obtained by Doupis et al Their research showed increased VEGF level in the serum of non-obese patients with diabetes, and in obese patients with diabetes.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Adipose tissue is considered to be an endocrine organ and releases hormones, enzymes and cytokines, including VEGF and IL-6 [14,15]. In 2010, Loebig et al observed a positive correlation between BMI and serum VEGF level [15]. A similar result was obtained by Doupis et al Their research showed increased VEGF level in the serum of non-obese patients with diabetes, and in obese patients with diabetes.…”
Section: Discussionmentioning
confidence: 69%
“…most patients were overweight or obese. Adipose tissue is considered to be an endocrine organ and releases hormones, enzymes and cytokines, including VEGF and IL-6 [14,15]. In 2010, Loebig et al observed a positive correlation between BMI and serum VEGF level [15].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Wada et al (2011) obtained similar findings to those in the SAPHIR study. Likewise, Loebig et al (2010), when examining the phenomenon of insulin resistance, observed a positive correlation between VEGF-A levels and BMI values, but only considered the parameters of hormonal balance without taking account of the presence of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bioavailable IGF-I is increased by hyperinsulinemia in obese individuals as a consequence of insulin induced decreases in IGF binding proteins [52]. Notably, VEGF is also induced by elevated insulin and IGF-I levels associated with obesity [55] and aggressive cancers [56,57].…”
Section: Insulin and Insulin Like Growth Factorsmentioning
confidence: 99%